2018
DOI: 10.1186/s12974-018-1117-5
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated overexpression of OTULIN ameliorates microglia activation and neuroinflammation by depressing the activation of the NF-κB signaling pathway in cerebral ischemia/reperfusion rats

Abstract: BackgroundIschemic stroke-induced neuroinflammation is mainly mediated by microglial cells. The nuclear factor kappa B (NF-κB) pathway is the key transcriptional pathway that initiates inflammatory responses following cerebral ischemia. OTULIN, a critical negative regulator of the NF-κΒ signaling pathway, exerts robust effects on peripheral immune cell-mediated inflammation and is regarded as an essential mediator for repressing inflammation in vivo. The effect of OTULIN on inflammatory responses in the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 74 publications
(87 reference statements)
1
39
0
Order By: Relevance
“…Immunity and inflammation are key elements that contribute to the pathobiology of stroke, and its caused-CI/RI and the secondary damage to brain tissues are closely associated with immunity and inflammation responses [5,6,7,8]. Previous research has shown that immunity and inflammation are integral parts of the pathogenesis of ischemic stroke [55,56,57]. Inflammatory signaling is activated and completed by blood-borne leukocytes that penetrate the brain during the ischemic phase [2].…”
Section: Discussionmentioning
confidence: 99%
“…Immunity and inflammation are key elements that contribute to the pathobiology of stroke, and its caused-CI/RI and the secondary damage to brain tissues are closely associated with immunity and inflammation responses [5,6,7,8]. Previous research has shown that immunity and inflammation are integral parts of the pathogenesis of ischemic stroke [55,56,57]. Inflammatory signaling is activated and completed by blood-borne leukocytes that penetrate the brain during the ischemic phase [2].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that an inflammatory response is involved in all stages of ischemia-reperfusion injury [68,69]. Once ischemia/reperfusion occurs, ROS production promotes the activation of complements, platelets and endothelial cells; activates inflammatory transcription factors and the release inflammatory signals [70]; and generates inflammatory factors, including IL-6, IL-1β, and TNF-α [68,69,70,71]. At the same time, because ROS causes neuronal cell death and the release of nucleosides, they can activate purine receptors on microglia and macrophages, leading to the aggregation of and infiltration by inflammatory cells to simultaneously induce inflammation and a series of secondary tissue damage, such as the destruction of the blood-brain barrier and cerebral edema [15,43,72].…”
Section: Protective Effects and Mechanismsmentioning
confidence: 99%
“…In addition, neutrophil adhesion to vascular endothelial cells inhibited the production of NO, as determined by the aggravation of cell edema (74). Leptin has an anti-inflammatory role (75,76); it activates the nuclear factor-κB pathway, inhibits the expression of pro-inflammatory factors [tumor necrosis factor (TNF)-α, IL-6, IL-1β] within 7 h and increases the expression of IL-10 (74,77) Within 100 min, the human body is able to recover from hypothermia and hypotension caused by ischemia/reperfusion injury (78). Within 90–240 min, TNF-α is inhibited.…”
Section: Protective Mechanisms Of Leptin In the Brainmentioning
confidence: 99%